Study of Fish Exploitation Pattern of River Bharathapuzha, Kerala, India - Renjithkumar, C. R.; Roshni, K.; Kurup, B. M. (Fishery Technology, 2021)
A total of 31 finfish species belonging to 7 orders and 28 genera and one shell fish species were recorded in the exploited pattern of Bharathapuzha river. Total annual fish landing from the Bharathapuzha river was quantified as 112.56 t. Highest landing was recorded during the post-monsoon season and lowest during the monsoon season. The main species contributed to the landing are Dawkinsia filamentosa (17.34 t), Systomus sarana (12.06 t), Hypselobarbus kurali (9.89 t), Parambassis dayi (8.39 t) and Wallago attu (7.61). Gibelion catla, Labeo rohita, Cirrhinus mrigala (Indian major carps) and Oreochromis mossambicus were the non-native species represented in the exploited fishery. Gill nets, cast nets, seine nets and hook and lines were the major fishing gears used in the river. Catch per unit effort (CPUE) recorded in gill net for major species were Pseudetroplus maculatus (0.75 kg h-1), Devario aequipinnatus (0.5 kg h-1), L. rohita (0.38 kg h-1), D. filamentosa (0.20 kg h-1) and S. sarana (0.18 kg h-1). The highest CPUE recorded in cast net was for Hypselobarbus kurali (0.51 kg h-1), Hyporhamphus xanthopterus (0.50 kg h-1), Mystus vittatus (0.38 kg h-1) and W. attu (0.29 kg h-1). In seine net high CPUE was recorded in Channa striata (0.17 kg h-1), L. rohita (0.16 kg h-1) and Etroplus suratensis (0.13 kg h-1).